Evaluacion del recurso suelo y agua (E.R.S.A) para el sistema de Gestión Ambiental del proyecto Agroforestal Perteneciente a Fundación M.A.R.C.O. Provincia de Chimborazo. - Ortiz Gavilanes, David Marcelo (2011)
It is called environmental management to all proceedings leading to the comprehensive management of the environmental system. In other words, and including the concept of sustainable development it is the strategy by which human activities are organized to affect the environment in order to achieve an adequate quality of life by preventing or mitigating the environmental problems.